2013
DOI: 10.1186/1532-429x-15-13
|View full text |Cite
|
Sign up to set email alerts
|

Normal variation of magnetic resonance T1 relaxation times in the human population at 1.5 T using ShMOLLI

Abstract: BackgroundQuantitative T1-mapping is rapidly becoming a clinical tool in cardiovascular magnetic resonance (CMR) to objectively distinguish normal from diseased myocardium. The usefulness of any quantitative technique to identify disease lies in its ability to detect significant differences from an established range of normal values. We aimed to assess the variability of myocardial T1 relaxation times in the normal human population estimated with recently proposed Shortened Modified Look-Locker Inversion recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
244
4
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(280 citation statements)
references
References 29 publications
28
244
4
4
Order By: Relevance
“…Using equation 3 in the Appendix and T 1b for men and for women, we estimated that the relative sex difference in pCBF ASL values in our data decreased from 12% to approximately 4%, which then is less than the PCMRI findings. In the same study, Piechnik et al 40 found no differences in T1 b values between HY (20 -30 years) and HE (60 -70 years) subjects, which indicates that the T1 b effect is not the dominating factor in explaining the large effect of aging on pCBF ASL . Motion artifacts during the ASL scan were not corrected, which might be a source of error in the pCBF ASL estimates.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Using equation 3 in the Appendix and T 1b for men and for women, we estimated that the relative sex difference in pCBF ASL values in our data decreased from 12% to approximately 4%, which then is less than the PCMRI findings. In the same study, Piechnik et al 40 found no differences in T1 b values between HY (20 -30 years) and HE (60 -70 years) subjects, which indicates that the T1 b effect is not the dominating factor in explaining the large effect of aging on pCBF ASL . Motion artifacts during the ASL scan were not corrected, which might be a source of error in the pCBF ASL estimates.…”
Section: Discussionmentioning
confidence: 87%
“…26,37 Previous studies have shown higher mean T1 b values (6%-9%) in women than in men, and the lower blood hematocrit level in women than in men may explain this observed sex difference in mean T1 b . [38][39][40] In a previous study, Piechnik et al 40 found significantly higher mean T1 b values in women than in men (1577 vs 1491 ms, respectively). Using equation 3 in the Appendix and T 1b for men and for women, we estimated that the relative sex difference in pCBF ASL values in our data decreased from 12% to approximately 4%, which then is less than the PCMRI findings.…”
Section: Discussionmentioning
confidence: 87%
“…This result concords with our own findings in a larger and multicenter cohort of healthy subjects, 33 as well accords with the subanalysis in subjects with low prevalence of cardiovascular risk factors in Multiethnic Study of Atherosclerosis (MESA) study (albeit reporting on extracellular volume fraction). 34 Piechnik et al 35 showed a mild inverse relationship between native T1 and age. Contrary to controls, native T1 increases with age in the presence of disease, suggesting a cumulative effect of disease process with time.…”
Section: )mentioning
confidence: 96%
“…Modern in-line processing provides registration tools to reduce motion artifacts before the computation of final T1 maps (motion-corrected or "MoCo MOLLI") [27]. A shortened Modified Look-Locker inversion recovery (shMOLLI) with shorter breath-holds has been validated and recently applied for cardiomyopathies [28,29].…”
Section: T1 Mapping With Modified Look-locker Inversion "Molli" Recoverymentioning
confidence: 99%